Cross‐talk between microRNAs, nuclear factor E2‐related factor 2, and heme oxygenase‐1 in ochratoxin A‐induced toxic effects in renal proximal tubular epithelial cells. Issue 3 (28th December 2012) - Stachurska, Anna; Ciesla, Maciej; Kozakowska, Magdalena; Wolffram, Siegfried; Boesch‐Saadatmandi, Christine; Rimbach, Gerald; Jozkowicz, Alicja; Dulak, Jozef; Loboda, Agnieszka
<x xml:space="preserve">Abstract</x> Scope Ochratoxin A (OTA) is a mycotoxin exhibiting nephrotoxic and potential carcinogenic activity. We investigated the cross‐talk between microRNAs, nuclear factor E2‐related factor 2 (Nrf2), and heme oxygenase‐1 (HO‐1) in ochratoxin A‐mediated effects. Methods and results In porcine renal proximal tubular cells, OTA increased expression of profibrotic transforming growth factors β (TGFβ) while concomitantly decreasing expression of Nrf2, HO‐1, and erythropoietin. Adenoviral overexpression of Nrf2 counteracted OTA‐mediated reduction in HO‐1 and erythropoietin expression and cell proliferation as well as increase in reactive oxygen species (ROS) generation and TGFβ expression. Additionally, inhibition of HO activity enhanced whereas adenoviral overexpression of HO‐1 reduced expression of TGFβ. Moreover, antioxidants, N‐acetyl‐cysteine and desferioxamine, prevented OTA‐mediated enhancement of ROS generation, and TGFβ expression. Finally, OTA modulated microRNA processing by upregulating LINeage protein 28 and DiGeorge syndrome critical region‐8, increasing the total pool of cellular microRNAs and elevating the expression of miR‐132 and miR‐200c. Inhibition of miR‐132 by specific antagomir restored the OTA‐driven reduction in Nrf2 expression. Moreover, anti‐miR‐132 and anti‐miR‐200c counteracted OTA‐mediated decrease in HO‐1 levels as well as increase in ROS production and TGFβ expression. Conclusion We showed that attenuation of Nrf2 and HO‐1 expression through induction of miR‐132 and miR‐200c by OTA elevates ROS levels and profibrotic TGFβ expression.